2012
DOI: 10.1155/2012/891893
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Pattern of Chinese Herbal Products for Breast Cancer in Taiwan: A Population-Based Study

Abstract: Background. Chinese herbal products (CHPs) given as a therapy for symptom relief have gained widespread popularity among women with breast cancer. The aim of this study was to analyze the utilization of CHP among women with breast cancer in Taiwan. Methods. The usage, frequency of services, and CHP prescribed for breast cancer among women with breast cancer were evaluated, recruited from a randomly sampled cohort of 1,000,000 beneficiaries from the National Health Insurance Research Database. The logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 21 publications
6
70
0
Order By: Relevance
“…In the present study, the most common diagnoses for CHM users of FBC patients were “malignant neoplasm of female breast” and “general symptoms”, such as nausea, vomiting, fatigue, etc. However, treatment for breast cancer accounted for only 21.8%, which is in accordance with the findings of the previous survey in Taiwan 14,15. This is significantly lower than the results from Shanghai, which found that more than 90% of FBC patients used CHM for fighting cancer 9.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, the most common diagnoses for CHM users of FBC patients were “malignant neoplasm of female breast” and “general symptoms”, such as nausea, vomiting, fatigue, etc. However, treatment for breast cancer accounted for only 21.8%, which is in accordance with the findings of the previous survey in Taiwan 14,15. This is significantly lower than the results from Shanghai, which found that more than 90% of FBC patients used CHM for fighting cancer 9.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study, conducted in Shanghai, the People’s Republic of China, showed that 76.8% of breast cancer patients used CHM therapy after a diagnosis of breast cancer 9. In Taiwan, Lai et al also found that 81.5% of female breast cancer (FBC) patients used TCM services and received CHM in 76.8% of visits during the 10-year study period 14. In the survey conducted by Lin and Chiu, 35.6% of breast cancer patients used TCM during the 1-year observation period in Taiwan, and CHM (80.5%) was the most commonly used therapy 15.…”
Section: Introductionmentioning
confidence: 99%
“…Shih C-C et al 23) 2012 33) In 1997∼2010, 9.25% patients with newly diagnosed acute myeloid leukemia and received radiotherapy and chemotherapy used TEAM 34) Colon cancer In 2004∼2008, 19.81% of newly diagnosed colon cancer patients used TEAM 35) In 2007, 26.9% of newly diagnosed colorectal cancer patients used TEAM 36) Head and neck cancer In 2000∼2011, 37.51% of newly diagnosed head and neck cancer patients used TEAM 37) Pediatric cancer In 2001∼2011, 62.37% of newly diagnosed pediatric cancer patients used TEAM 38) Breast cancer In 1999∼2008, 81.55% of newly diagnosed breast cancer patients used TEAM 39) In 2007, 35.6% of breast cancer patients used TEAM 40) In 2009, 37.33% of breast cancer patients used TEAM 41) Uterine fibroid In 2000∼2003, 73.33% of newly diagnosed uterine fibroid patients used TEAM 42) In 1996∼2010, 25.84% of uterine fibroid patients used TEAM 43) In 2002∼2010, 87.08% of newly diagnosed uterine fibroid patients used TEAM 44) Prostate cancer In 1996∼2008, 38.8% of prostate cancer patients used TEAM 45) In 1998∼2003, 64.5% of newly diagnosed prostate cancer patients used TEAM 46) In 2003∼2008, 52.6% of prostate cancer patients used TEAM 47) In 2007, 22.4% of outpatients with prostate cancer received prescription of herbal medicine 48) Lung cancer In 1996∼2010, Of the lung cancer patients, 31.17% of the operation patients and 26.32% of the non-operation patients used TEAM 49) Endocrine, nutritional and metabolic diseases, and immunity disorders (3.59%) Hyperlipidemia In 2003∼2009, 82.95% of hyperlipidemia patients used TEAM 50) Diabetes mellitus In 2000∼2011, 20.55% of type I diabetes mellitus patients used TEAM 51) In 1998∼2008, 77.91% of newly diagnosed type II diabetes mellitus adult patients used TEAM 52) Mental disorders (3.10%)…”
Section: 대만의 보편적 Team 이용 관련 연구mentioning
confidence: 99%
“…In East Asian countries, traditional Chinese medicine (TCM) is another option in addition to or instead of Western medicine for treating constipation (Camilleri and Bharucha, 2010;Candy et al, 2011;Chey et al, 2011). In many of these countries, especially Taiwan, TCMs are frequently prescribed for the treatment of many chronic diseases (Jong et al, 2010;Lai et al, 2012;Shih et al, 2012). According to a survey from a cohort of one million randomly sampled cases from the National Health Insurance database in Taiwan, the Chinese herbal formula San-Huang-Xie-Xin-Tang (SHXXT) is widely used for the treatment of constipation (Jong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, convenient pharmaceutical herbal products are also used instead of the traditional herbal decocting process. Pharmaceutical herbal products are mainly made by industrial manufacturing methods of decoction, filtration, extraction, concentration, spray or fluid bed granulation, coating and filling (Jong et al, 2010;Lai et al, 2012;Shih et al, 2012).…”
Section: Introductionmentioning
confidence: 99%